Use of Social Media for Scholarly Communication - Nurul Fikriati Ayu Hapsari; Iwin Ardyawin; Rohana; Dodi Firdausi Nuzula; Hasnah Hashim (Record and Library Journal, 2023)
Background of the study: Social media is widely used in the current educational context and significantly affects scholarly communication. This informal scientific communication activity is an activity that is not "covered" in the world of educational curricula and is more directed at increasing the scientific group by making scientific discussions. Until now, scientific discussion activities in tertiary institutions are still carried out massively by students, including students on the island of Lombok. Purpose: The purpose of this study was to measure the level of WhatsApp users for scientific communication and the effect of user motives on the level WhatsApp used for scientific communication. Method: Using a quantitative approach with a survey method, it was conducted for seventy-five (75) library students who were actively using WhatsApp for scientific communication. Findings: The majority of respondents indicated that WhatsApp has a high usage rate for scientific communication purposes. The results showed that information motives and social interaction motives have a significant effect on the level of WhatsApp used for scholarly communication, while personal identity motives have no effect. Conclusion: The conclusion is that students have not maximized the use of social media for scientific communication. Students do activities to searching and searching information but do not carry out activities to build interactions such as holding discussions or collaborating to produce scientific work with other academics.